A palaeomagnetic study of the volcanic rocks of El-Mane mountain, south of Damascus – Syria - D. H. Tarling; J. M. Abou-Deeb (Geofísica Internacional, 2005)
Previously reported palaeomagnetic data from region El Mane Mountain of Syria are supplemented by thermal demagnetisation studies of 46 new sites (14 flow units). Sites with strong within and between sample consistency are arranged stratigraphically and combined with previous palaeomagnetic and radiometric data to establish a preliminary magnetostratigraphic chronology. This correlates closely with polarity chrons 5Dr to 6An.1r of the Geomagnetic Polarity Time Scale. The volcanism appears to have occurred spasmodically throughout this 3 Ma period, probably in relation to the irregular development of new fracture systems rather than quasi-intermittent injection of magma into local chambers. It is confirmed that the spatial-temporal variations of the geomagnetic field did not correspond closely to that of an axial geocentric dipole in this region at this time, but was possibly influenced by a strong and persistent non-dipole component. This affected the inclinations observed during both Normal and Reversed periods. Nonetheless, the declinations were more affected during times of Normal polarity than during times of Reversed polarity. On this basis, caution is urged in the interpretation of palaeomagnetically determined tectonic rotations, during this time in the Middle Eastern region.